First Report of Aprostocetus asthenogmus (Hymenoptera: Eulophidae) in South America and Parasitizing Eggs of Triatominae Vectors of Chagas Disease - Claudiney Biral dos Santos; Marcelo Teixeira Tavares; Gustavo Rocha Leite; Adelson Luiz Ferreira; Leonardo de Souza Rocha; Aloísio Falqueto (Journal of Parasitology Research)
We report for the first time the parasitism of eggs of two triatomine Chagas disease vectors, Triatoma infestans and T. vitticeps, by the microhymenopterous parasitoid Aprostocetus asthenogmus. We also describe the first identification of this parasitoid in South America. A. asthenogmus were captured near unparasitized triatomine colonies in the municipality of Vitória, state of Espírito Santo, Brazil, and placed into pots with recently laid triatomine eggs. After 24 days, we observed wasps emerging from T. infestans and T. vitticeps eggs. Several characteristics of this parasitoid species suggest that it could be a potential biological control agent of triatomine species.